Peran Budaya Organisasi dalam Meningkatkan Loyalitas Anggota - Nova Wahyu Dhiyanto; Dwi Sri Astuti (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to discuss the role of organizational culture in increasing member loyalty. Organizational culture is a series of values, norms and beliefs that are implemented jointly by a group of organizational members and are manifested in everyday life. Member loyalty is an important factor in maintaining organizational stability and productivity in the long term. The method I used in this research was a quantitative approach by distributing questionnaires to members of the organization as respondents. The results of the analysis show that elements of organizational culture such as open communication, inspirational leadership, and strong shared values ​​have a significant influence on member loyalty. These findings confirm that strengthening a positive organizational culture can be an effective strategy in building member commitment and attachment to the organization.